Lavado de activos: necesidad de un trato de excepción - Chasillacta Zurita, Andrés Esteban (2018)
The purpose of this investigation is to answer the following question: is it legitimate to grant an exception treatment to the crime of money laundering and in particular to its unjustified enrichment. This infraction has gained vital importance in recent years due to the great scourge it causes in society, which is why several international organizations have tried to issue recommendations, in order to seek a unification in the legislation that penalizes this activity. This academic essay is useful to seek a solution within the Ecuadorian normative framework, to eliminate impunity and the limitations of the Office of the Prosecutor in the investigation of this conduct relevant to criminal law. The method used was the legal analysis of the behavior, the mechanisms that are generally used to launder money, which corresponds to the real problem of this action, as the criminal organizations seek to eliminate all traces generated by the assets produced through the criminal operations that perform. At the end of the Work has been obtained the analysis approach that should be made to the phrase illicit origin within the Ecuadorian framework, in accordance with the international treaties signed, this is the unjustified increase of heritage and the need for probanza by the Attorney General of this fact, to safeguard the rights of the accused.